Assessment of fixed‐duration therapies for treatment‐naïve Waldenström macroglobulinemia. Issue 8 (22nd May 2021) - Abeykoon, Jithma P.; Zanwar, Saurabh; Ansell, Stephen M.; Muchtar, Eli; He, Rong; Greipp, Patricia T.; King, Rebecca L.; Ailawadhi, Sikander; Paludo, Jonas; Larsen, Jeremy T.; Habermann, Thomas M.; Inwards, David; et al.
Abstract: Comparative data guiding initial therapy for Waldenström macroglobulinemia (WM), an infrequently encountered non‐Hodgkin lymphoma, are sparse. We evaluated three commonly used rituximab‐based frontline regimens: rituximab‐bendamustine (R‐Benda); dexamethasone, rituximab, cyclophosphamide (DRC); and bortezomib, dexamethasone, rituximab (BDR) in 220 treatment‐naïve patients with WM, seen at Mayo Clinic between November 1, 2000 and October 31, 2019. The median follow‐up was 4.5 (95%CI: 4–5) years. The R‐Benda cohort (n = 83) demonstrated superior overall response rate (ORR: 98%), in comparison to DRC (n = 92, ORR: 78%) or BDR (n = 45, ORR: 84%) cohorts, p  = 0.003. Similarly, longer progression‐free survival (PFS) was evident with R‐Benda use [median 5.2 vs. 4.3 (DRC) and 1.8 years (BDR), p  < 0.001]. The time‐to‐next therapy (TTNT) favored R‐Benda [median, not‐reached, 4.4 (DRC) and 2.6 years (BDR), p  < 0.001). These endpoints were comparable between the DRC and BDR cohorts. Overall survival (OS) was similar across the three cohorts, p  = 0.77. In a subset analysis of 142 patients genotyped for MYD88 L265P mutation, the ORR, PFS and TTNT were unaffected by the patients' MYD88 signature within each cohort. In conclusion, ORR, PFS and TTNT with R‐Benda are superior compared to DRC or BDR in treatment‐naïve patients with active WM. The patient outcomes with any one of these three regimens are unaffected by the MYD88 L265P mutation status.